PENGARUH MODEL DISCOVERY LEARING TERHADAP HASIL BELAJAR MATEMATIKA PADA MATERI PECAHAN SISWA KELAS IV SD MIS NURUL HUDA - Rahmawati; Nasrun; Sirajuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of implementing the Discovery Learning model on mathematics learning outcomes in the topic of fraction addition for fourth-grade students at MIS Nurul Huda. This research used a quantitative approach with a Pre-Experimental design in the form of a One Group Pretest-Posttest Design. The research sample consisted of 23 fourth-grade students of MIS Nurul Huda. The instrument used was a learning outcome test in the form of pretest and posttest questions on the topic of fraction addition. Data collection was conducted through tests administered before and after the treatment. The data obtained were analyzed using descriptive statistics and the Wilcoxon Signed Ranks Test with the help of SPSS version 25. The results of the study showed that the average pretest score was 21.74, which was categorized as very low, and all students (100%) had not yet reached the Minimum Mastery Criterion (KKM) of 75. After the implementation of the Discovery Learning model, the average posttest score increased to 83.70, which was categorized as high, and 19 students (82.61%) achieved learning mastery. The results of the Wilcoxon test showed a significance value of 0.000 < 0.05, so it can be concluded that there is a significant effect of the implementation of the Discovery Learning model on students’ mathematics learning outcomes.